Tradisi Rongkat Kandung Kembar dalam Kumpulan Cerpen Kembang Selir Karya Muna Masyari: Kajian Semiotika - Rilasari, Dani; Faizah, Inayah Isnaini; Astuty, Astuty (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to describe the Rokat Birth Kembar tradition from the collection of short stories Kembang Selir by Muna Masyari along with the symbols and meanings contained in this tradition. The method used in this research is descriptive qualitative because the aim of the research is to describe the Rokat Kandung Kembar tradition and the meaning contained therein. This research includes an anthropological study of literature. This research data collection technique uses note-reading techniques. Through semantic analysis, the results found were that jackfruit seeds symbolize fertility and hope, while white mori cloth shows purity and adherence to tradition. Flip-flops reflect simplicity while rice and cooked eggs symbolize togetherness in life